2016
DOI: 10.1016/j.cviu.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Localization and tracking in known large environments using portable real-time 3D sensors

Abstract: a b s t r a c tEgo-motion estimation and localization in large environments are key components in any assistive technology for real-time user orientation and navigation. We consider the case where a large known environment is explored without a priori assumptions on the initial location. In particular we propose a framework that uses a single portable 3D sensor to solve the place recognition problem and continuously tracks its position even when leaving the known area or when significant changes occur in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The navigation system extracts ground plane to reduce drift imposed by the head-mounted RGB-D sensor and the paper demonstrated that the traversability map works more robustly with a light-coding sensor than with a stereo pair in low-textured environments. As for another indoor localization application, Sánchez detected floor and navigable areas to efficiently reduce the search space and thereby yielded real-time performance of both place recognition and tracking [39]. …”
Section: Related Workmentioning
confidence: 99%
“…The navigation system extracts ground plane to reduce drift imposed by the head-mounted RGB-D sensor and the paper demonstrated that the traversability map works more robustly with a light-coding sensor than with a stereo pair in low-textured environments. As for another indoor localization application, Sánchez detected floor and navigable areas to efficiently reduce the search space and thereby yielded real-time performance of both place recognition and tracking [39]. …”
Section: Related Workmentioning
confidence: 99%
“…Mobile laser scanning systems significantly increase the efficiency of 3D laser scanning applied to nuclear safeguards verification. They also allow computing the position of the sensor with respect to the acquired map [17]. This technique, known as Simultaneous Localisation and Mapping (SLAM), can be used for location-based services in indoor environments as described below.…”
Section: D Laser Scanningmentioning
confidence: 99%
“…Heron is a slam based mobile mapping system developed by an Italian Company (Gexcel) in collaboration with the laboratories of the European Commission at the Joint Research Centre of Ispra (Italy) (Sánchez C. et al, 2016). Heron is a wearable Mobile Mapping System that supports Indoor and Outdoor mapping.…”
Section: The Heron Systemmentioning
confidence: 99%